56 The Lung Impedance Monitoring in Treatment of Chronic Heart Failure: Results from the Limit-Chf Study. (6th June 2015) - Domenichini, Giulia; Rahneva, Tsveta; Diab, Ihab; Dhillon, Onkar; Baker, Victoria; Hunter, Ross; Earley, Mark; Schilling, Richard
Abstract : Introduction: To assess the usefulness of intra-thoracic impedance monitoring (IIM) alerts in guiding medication therapy in chronic heart failure (CHF) patients (pts) to prevent hospitalisations/unplanned visits. Methods: CHF pts with OptiVol® or CorVue™ capable ICDs were randomised to either the active group (IIM alarm turned on and diuretic dose increased by 50% for one week) or the control group (IIM alarm turned off). The primary endpoint was the number of hospitalisations per pt at 1 year. The NYHA class, 6 min walk test (6MWT), BNP and Minnesota Living with HF (MLWHF) questionnaire score were collected at baseline and follow-up (f-up). Results: 80 pts were included and 71 reached 1 year f-up (7 pts died, 1 pt was lost at f-up and 1 pt was excluded from analysis since the congestion data were not collected by the device). The baseline characteristics and study outcomes are shown in the Table 1. After a median f-up of 13 months (IQR 12–14), there were 1.72 ± 1.45 alerts in the active group vs. 1.13 ± 1.0 in the control group, p = 0.07. In the active group 60.9% (42/69) of alerts led to increasing the diuretic dose. There was a total of 11 hospitalisations in the active group vs. 6 in the control group without significant differences in the number of episodes per pt (0.28 ± 0.85 vs. 0.15 ± 0.43, p = 0.95). There were no unplanned visits in the active group vs. 0.08 ± 0.27 per pt in the control group, p = 0.08. There was a moderate but significant reduction in HF related quality of life scores in the active group. Conclusion: In this study IIM did not reduce emergency treatment of HF however there was a positive impact on quality of life. This technology may have a useful role in managing HF pts with implantable devices.